Exploring the mechanism of Lingbao Huxin Dan in the treatment of bradycardia based on atrioventricular node electrical signal conduction - Jing Zhang; Guobin Zheng; Shangjing Liu; Yaodong Miao; Shu Yang; Sheng Li; Zhihui Yang; Danping Zhuo; Rui Guo; Yang Guo; Rongjiang Shao; Yunqing Hua; et al. (Journal of Holistic Integrative Pharmacy)
Background: Prolonged bradycardia leads to inadequate pumping of the heart, causing myocardial ischemia, which in turn affects cardiac function. Depending on its clinical features, improving the AV node conduction block may be an important tool to inhibit the progression of the disease. Lingbao Huxin Dan, which consists of several traditional Chinese medicines, is used for conditions similar to bradycardia and may be a potential therapeutic agent for bradycardia. In this experiment, we investigated its therapeutic significance and possible therapeutic targets for sinus bradycardia. Methods: The bradycardia model of SD rats was prepared by using acetylcholine, propranolol, and verapamil respectively, and treated with Lingbao Huxin Dan for 3 weeks. At the end of treatment, the rats' ECG was recorded using a PV-LOOP heart rate recorder. The hearts and serum samples were collected to detect heart rate and related gene expression which were screened through network pharmacology analysis, as well as to evaluate the effect of Lingbao Huxin Dan on ion channels in the cardiac conduction system. Results: Lingbao Huxin Dan improved the heart rate in the bradycardia model of SD rats and inhibited AV node conduction block by targeting ion channel proteins in the cardiac conduction system. The underlying molecular mechanism may be the activation of the β-adrenergic receptor-dependent cAMP/PKA signaling pathway targeted to enhance the expression of the pacing channel HCN4. In addition, Lingbao Huxin Dan prevented the deterioration of bradycardia by promoting the production of the oxygen radical scavenger SOD and inhibiting the upregulation of LDH due to cardiomyocyte damage. Conclusions: Our study proved that Lingbao Huxin Dan alleviated bradycardia by downregulating CX45 and enhancing the expression of HCN4, ADRβ1, and TRPM7 to shorten the atrioventricular node induction period and improve sinoatrial node signaling. In addition, Lingbao Huxin Dan relieved myocardial injury induced by bradycardia by reducing the level of oxygen free radicals in the cardiac microenvironment.